CD133+ cells in pulmonary arterial hypertension. Issue 2 (21st April 2016) - Foris, Vasile; Kovacs, Gabor; Marsh, Leigh M.; Bálint, Zoltán; Tötsch, Martin; Avian, Alexander; Douschan, Philipp; Ghanim, Bahil; Klepetko, Walter; Olschewski, Andrea; Olschewski, Horst
Circulating mononuclear cells may play an important role for the vascular remodelling in pulmonary arterial hypertension (PAH), but studies addressing multiple progenitor populations are rare and inconsistent. We used a comprehensive fluorescence-activated cell sorting analysis of circulating mononuclear cells in 20 PAH patients and 20 age- and sex-matched controls, and additionally analysed CD133 + cells in the lung tissue of five PAH transplant recipients and five healthy controls (donor lungs). PAH patients were characterised by increased numbers of circulating CD133 + cells and lymphopenia as compared with control. In PAH, CD133 + subpopulations positive for CD117 or CD45 were significantly increased, whereas CD133 + CD309 +, CD133 + CXCR2 + and CD133 + CD31 + cells were decreased. In CD133 + cells, SOX2, Nanog, Ki67 and CXCR4 were not detected, but Oct3/4 mRNA was present in both PAH and controls. In the lung tissue, CD133 + cells included three main populations: type 2 pneumocytes, monocytes and undifferentiated cells without significant differences between PAH and controls. In conclusion, circulating CD133 + progenitor cells are elevated in PAH and consist of phenotypically different subpopulations that may be up- or downregulated. This may explain the inconsistent results in the literature. CD133 + type 2 pneumocytes in the lung tissue are not associated with circulating CD133 + mononuclear cells. PAH patients are characterised by lymphopenia and increased numbers of CD133 + cells http://ow.ly/YNfQE